Characterization of Marcellus Shale and Huntersville Chert before and after exposure to hydraulic fracturing fluid via feature relocation using field-emission scanning electron microscopy. (15th October 2016) - Dieterich, Matthew; Kutchko, Barbara; Goodman, Angela
Abstract: Two sets of experimental in situ fluid–rock interaction studies were implemented to understand the interactions between hydraulic fracturing fluid and rocks of the Marcellus Shale gas play. Marcellus Shale and Huntersville Chert core samples were exposed to synthetically prepared fracturing fluid and recycled fracturing fluid from the field, respectively, and examined before and after in situ exposure using surface relocation techniques via high-resolution field-emission scanning electron microscopy (FE-SEM) to investigate chemical or physical alterations. Results indicate that in situ pressure promoted fracture growth along the sedimentological (horizontal) bedding plane of the Marcellus Shale samples. Moreover, calcium carbonate (CaCO3 ) dissolution was observed and gypsum (CaSO4 ∗ 2H2 O) appeared to precipitate both on the surface and in the numerous fractures. Barite (BaSO4 ), strontianite (SrCO3 ), celestine (SrSO4 ), and apatite (CaPO4 ) formed a unique pattern of precipitates on the surface of the Huntersville Chert samples. Additionally, Rhenium and rare earth element (REE) Europium were identified in minerals which precipitated on the Huntersville Chert surface identified by FE-SEM spectral analysis.